Clinical and Genetic Spectrum of a Large Cohort With Total and Sub-total Complement Deficiencies - El Sissy, Carine; Rosain, Jérémie; Vieira-Martins, Paula; Bordereau, Pauline; Gruber, Aurélia; Devriese, Magali; de Pontual, Loïc; Taha, Muhamed-Kheir; Fieschi, Claire; Picard, Capucine; Frémeaux-Bacchi, Véronique (Frontiers in Immunology, 2019)
The complement system is crucial for defense against pathogens and removal of dying cells or immune complexes. Thus, clinical indications for possible complete complement deficiencies include among others recurrent mild or serious bacterial infections as well as autoimmune diseases. The diagnostic approach includes functional activity measurements of the classical (CH50) and alternative pathway (AP50) and the determination of the C3 and C4 levels, followed by the quantitative analysis of individual components or regulators. When biochemical analysis reveals the causal abnormality of the complement deficiency, molecular mechanisms remains frequently undetermined. Here, using direct sequencing analysis of the coding region we report the pathogenic variants spectrum that underlie the total or subtotal complement deficiency in 212 patients. We identified 107 different hemizygous, homozygous, or compound heterozygous pathogenic variants in 14 complement genes (C1Q (n=1), C1r (n=3), C1s (n=2), C2 (n=12), C3 (n=5), C5 (n=12), C6 (n=9), C7 (n=17), C8 (n=7), C9 (n=3), CFH (n=7), CFI (n=18), CFP (n=10), CFD (n=2). Molecular analysis identified 17 recurrent pathogenic variants in 6 genes (C2, CFH, C5, C6, C7 and C8). More than half of the pathogenic variants identified in unrelated patients were also found in healthy controls from the same geographic area. Our study confirms the strong association of meningococcal infections with terminal pathway deficiency and highlights the risk of pneumococcal and auto-immune diseases in the classical and alternative pathways. Results from this large genetic investigation provide evidence of a restricted number of molecular mechanisms leading to complement deficiency and describe the clinical potential adverse events of anti-complement therapy.